Nitroglycerin and Iloprost Improve Mitochondrial Function in Colon Homogenate Without Altering the Barrier Integrity of Caco-2 Monolayers - Herminghaus, Anna; Eberhardt, Rebecca; Truse, Richard; Schulz, Jan; Bauer, Inge; Picker, Olaf; Vollmer, Christian (Frontiers in Medicine, 2018)
Locally applied nitroglycerin (nitric oxide (NO) donor) and iloprost (analogue of prostacyclin PGI2) improve regional gastric oxygenation and nitroglycerin preserves gastric mucosal barrier integrity. This suggests direct effects of these substances on oxygenation and barrier function. The aim of this study was to analyze the effect of iloprost and nitroglycerin on intestinal mitochondrial function and on mucosal barrier function in vitro. Mitochondrial oxygen consumption (respirometry) was determined in colon homogenates from 16 healthy rats before (control) and 15 min after incubation with nitroglycerin (25 and 250 µg/ml) and iloprost (0.1 and 1 µg/ml). State 2 (substrate-dependent oxygen consumption) and state 3 respiration (ADP-dependent oxygen consumption) were assessed and ADP/O ratio (ADP added/oxygen consumed) for complex I and II were calculated. For permeability measurement we used the Caco-2 monolayer. Fluorescein sulfonic acid (FS) (200 µg/ml) and the drugs were administered into the apical compartment of the transwell chamber. After 48h, FS translocation was assessed as basolateral/apical FS. Both concentrations of nitroglycerin and iloprost reduced state 3 by stimulation via both complexes. Iloprost increased ADP/O ratio after stimulation via both complexes at the higher (1µg/ml), and only via complex II at the lower concentration (0.1µg/ml). Nitroglycerin increased ADP/O ratio only at the higher concentration (250µg/ml) after stimulation via complex I. Neither nitroglycerin nor iloprost influenced FS translocation. Iloprost and nitroglycerin reduce the maximal mitochondrial respiration and improve the efficacy of oxidative phosphorylation in colon homogenates. Both drugs have no direct influence on mucosal barrier integrity of Caco-2 monolayers.